Theoreticalaspects ofinformation war and national security - A. V. Shumka (Granì, 2015)
A wide and comprehensive analysis of methods of conducting information war to create an effective mechanism of counteraction has extremely important significance. Information warfare acts committed to achieve information superiority in support of national military strategy due to the impact of information and information systems enemy while ensuring the security of its own information and information systems. Today the term «information war» is used in two areas: in the broadest sense to determine confrontation in the information sphere in the media to achieve various political goals; in a narrow sense to determine the military confrontation, military information sector to achieve unilateral advantages in obtaining, collecting, processing and using information on the battlefield. Actions connected with maintenance of information security should include: observation, analysis, evaluation and prognosis of threats and hazards;  working out strategy and tactics, planning attack prevention, strengthening of potential relationships, gain resources information security;  selection of forces and means opposition, neutralization, prevent attacks and minimize damage from the attack; actions of ensuring information security;  managing the consequences of the incident (cyber attacks, information operations, information warfare). Organization of effective ensuring information security system provides centralized control of specific functions that provide monitoring and control of all components of the national information space.